The eye of the world - Jordan, Robert, 1948-2007 (Jordan, Robert. Wheel of time, 2020)
When she arrives in a small village in the Two Rivers, Moiraine discovers three young men, each of whom might be the long-awaited and reviled Chosen One, the Dragon Reborn. But she is not the only stranger new to the village, nor the only one searching. In a race against time and the agents of the Shadow, she must guide her charges through lands of myth and legend, toward allies both new and old, and into the footsteps of prophecy.